2001
DOI: 10.1046/j.1440-1819.2001.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential judgement of static facial expressions of emotions in three cultures

Abstract: Judging facial expressions of emotions has important clinical value in the assessment of psychiatric patients. Judging facial emotional expressions in foreign patients however, is not always easy. Controversy has existed in previous reports on cultural differences in identifying static facial expressions of emotions. While it has been argued that emotional expressions on the face are universally recognized, experimental data obtained were not necessarily totally supportive. Using the data reported in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 10 publications
3
25
0
Order By: Relevance
“…Therefore, our results need to be replicated in a larger sample to allow comparison between Asian subjects of different ethnicities. At the moment, our data support the assumption of Huang et al [33] suggesting that particularly expressions of negative emotions, here anger, might be strongly influenced by so-called nonverbal dialects in expression style. Additionally, behavioral performance and choice of response might also be influenced by cultural stereotypes, in particular by the cultural evaluation of negative emotions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, our results need to be replicated in a larger sample to allow comparison between Asian subjects of different ethnicities. At the moment, our data support the assumption of Huang et al [33] suggesting that particularly expressions of negative emotions, here anger, might be strongly influenced by so-called nonverbal dialects in expression style. Additionally, behavioral performance and choice of response might also be influenced by cultural stereotypes, in particular by the cultural evaluation of negative emotions.…”
Section: Discussionsupporting
confidence: 90%
“…[47,60,61] and some studies even suggest that powerful emotions are more intensely experienced and expressed by men, while women rather experience emotions associated with powerlessness, such as fear, sadness and shame e.g., [62]. Despite this gender issue, some cross-cultural studies also indicate that Caucasian expressions of anger are less accurately recognized by Asian participants than by Caucasian subjects, in particular Caucasian Americans e.g., [33,41]. Interestingly, Huang et al also observed an inter-Asian difference in anger recognition, with Chinese subjects performing significantly better than Japanese subjects when confronted with Japanese and Caucasian expressions of anger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last two or three decades, the issue of the universality of emotional facial expression has been addressed by several researchers. A large body of research has confirmed that people in many different cultures can reliably identify the emotional category displayed by static facial expressions (Ekman et al, 1987;Mandal, Bryden & Bulman-Fleming, 1996;Matsumoto et al, 2002, among others), even though some cross cultural studies failed to obtain high percentages of accurate recognition (for example, Huang, Tang, Helmeste, Shioiri, & Someya, 2001). The existence of crosscultural differences in judging facial expressions of emotions has crucial implications in many fields, be it of communication (Planalp, 1999) or clinical examination (Gepner, Deruelle, & Grynfeltt, 2001), especially because the specific emotional behaviours of each culture can lead to misattributions from a foreign observer and generate detrimental consequences.…”
mentioning
confidence: 99%
“…Fearful expressions are particularly significant cues in this process, as they often predict the presence of a threat in the immediate surrounding (Waters, Lipp, & Spence, 2004;Mogg & Bradley, 1998). However, the meaning of facial expressions is not always clear cut, and may depend on personal idiosyncrasies and cultural codes (Huang, Tang, Helmeste, Shioiri, & Someya, 2001;Shioiri, Someya, Helmeste, & Tang, 1999), leading to individual difference in where uncertainty is aroused in the process of interpreting oneʼs social context. Thus, uncertainty is an attribute that differs conceivably from one individual to another, and in danger situations, may result in hesitation, which hinders the ability to generate a quick and effective action.…”
Section: Introductionmentioning
confidence: 99%